(Against) Closing Children’s Homes (Archives of Criminology, 2008)
The underlying idea of the article is an attempt to answer whether the existence of children’s homes in an unchangeable and outdated form, developed under the previous system, is justified. The author wrote the article because he was urged to comment on the discussion caused by numerous media messages concerning the protection of the rights of children in institutions. The motive for this was the growing inaccuracies and oversimplifications that lacked careful analysis. Referring to his own experience, Marek Andrzejewski calls attention to the common contemporary underestimation of the usefulness of educational institutions. The author suggests that the failures of institutions do not lead to the necessary criticism and that the complexity of the institution of foster care gets lost in superficial public debate. The text cites the aftermath of a discussion that began in 1998 with a media campaign under the slogan of Let’s close children’s homes by the weekly magazine Polityka. As a result, a dozen or so articles appeared in the press arguing for the introduction of a modern approach to placing children in foster families and in care and educational institutions. The new approach was to support dysfunctional families. The public debate emphasised the need to expand the range of activities aimed at the parents and the rest of the family of a foster child, and to move away from focussingexclusivelyon the minor placed in an institution. According to the author, the new goal was to reintegrate the whole family from which the legal guardians of the child had previously been excluded. The text also presents the effects of the foster care reform initiated by the Buzek government, which entrusted the responsibility for running foster care centres and foster families to local governments, thereby establishing the district family assistance centres. The author cites arguments for not closing down the children’s homes, such as the well-established tradition of such institutions in democratic countries that respect human rights, the need to individually tailor the form of separatinga child from the family without using foster services that may prove harmful to and incompatible with the situation of a particular child, and the strong local presence of the institution. At the same time, Andrzejewski emphasises that not all children’s homes incorporate contemporary solutions in their work. For example, graduates of educational faculties who are not prepared to work in the institution, despite their enthusiasm and willingness, are not taught how to work with families. In his conclusions, the author warns against an antagonistic perception of institutional and family forms of foster care, which should not be pitted against each other. Andrzejewski suggests that more emphasis should be placed on the way of working in both types of foster care. Fundamental to this should be a move away from archaic forms of work to contemporary methods.